Species interactions increase the temporal stability of community productivity in Pinus sylvestris–Fagus sylvatica mixtures across Europe. (1st February 2017) - del Río, Miren; Pretzsch, Hans; Ruíz‐Peinado, Ricardo; Ampoorter, Evy; Annighöfer, Peter; Barbeito, Ignacio; Bielak, Kamil; Brazaitis, Gediminas; Coll, Lluís; Drössler, Lars; Fabrika, Marek; Forrester, David I.; et al.
Summary: There is increasing evidence that species diversity enhances the temporal stability (TS) of community productivity in different ecosystems, although its effect at the population and tree levels seems to be negative or neutral. Asynchrony in species responses to environmental conditions was found to be one of the main drivers of this stabilizing process. However, the effect of species mixing on the stability of productivity, and the relative importance of the associated mechanisms, remain poorly understood in forest communities. We investigated the way mixing species influenced the TS of productivity in Pinus sylvestris L. and Fagus sylvatica L. forests, and attempted to determine the main drivers among overyielding, asynchrony between species annual growth responses to environmental conditions, and temporal shifts in species interactions. We used a network of 93 experimental plots distributed across Europe to compare the TS of basal area growth over a 15‐year period (1999–2013) in mixed and monospecific forest stands at different organizational levels, namely the community, population and individual tree levels. Mixed stands showed a higher TS of basal area growth than monospecific stands at the community level, but not at the population or individual tree levels. The TS at the community level was related to asynchrony between species growth in mixtures, but not to overyielding nor to asynchrony between species growth in monospecific stands. Temporal shifts in species interactions were also related to asynchrony and to the mixing effect on the TS. Synthesis . Our findings confirm that species mixing can stabilize productivity at the community level, whereas there is a neutral or negative effect on stability at the population and individual tree levels. The contrasting findings regarding the relationships between the temporal stability and asynchrony in species growth in mixed and monospecific stands suggest that the main driver in the stabilizing process may be the temporal niche complementarity between species rather than differences in species' intrinsic responses to environmental conditions. Abstract : Our findings confirm that species mixing can stabilize productivity at the community level but not at the population and tree levels. The different relationships between the mixing effect on the temporal stability and species asynchrony in mixed and monospecific stands suggests that temporal niche complementarity between species may be the main driver rather than differences in species' intrinsic responses to environmental conditions.